Effect of surgery for encapsulating peritoneal sclerosis on mortality in patients undergoing peritoneal dialysis: A meta-analysis - Wei Huan; Gan Wenyuan; Liu Changxuan; Chen Wenli (Journal of International Medical Research)
Objective This study aimed to evaluate the effect of surgical versus nonsurgical treatment on mortality in patients with encapsulating peritoneal sclerosis who underwent peritoneal dialysis. Methods A comprehensive search using PubMed, Google Scholar, MEDLINE, Science Direct, Scopus, and CNKI databases was conducted to extract relevant data based on predefined inclusion criteria. RevMan5.2 was applied to analyze and compare the effect of surgical versus nonsurgical treatment on mortality in patients with encapsulating peritoneal sclerosis who underwent peritoneal dialysis. Results A total of 7 studies involving 70 surgical and 57 nonsurgical patients were included, with 61.4% females and 38.6% males. Among them, 69 were Asian and 58 were European patients, with 37.7% and 75.9% of Asian and European patients accepting surgical treatment, respectively. Pooled data analysis indicated that surgical treatment was associated with significantly lower mortality than nonsurgical treatment in patients with encapsulating peritoneal sclerosis (odds ratio = 0.25, 95% confidence interval: 0.11–0.57, Z = 3.29; P  =   0.001). Subgroup analysis revealed that Asian patients who accepted surgical treatment had significantly lower mortality than those receiving nonsurgical treatment (odds ratio = 0.19, 95% confidence interval: 0.06–0.57, Z = 2.93; P  =   0.003), whereas no significant difference was observed in mortality between surgical and nonsurgical treatments in European patients (odds ratio = 0.38, 95% confidence interval: 0.10–1.41, Z = 1.45; P  =   0.15). Conclusions Surgical treatment was associated with reduced mortality in patients with encapsulating peritoneal sclerosis compared with nonsurgical treatment; however, this benefit was more significant in Asian patients than in European patients.